2003
DOI: 10.1128/jcm.41.6.2395-2400.2003
|View full text |Cite
|
Sign up to set email alerts
|

Several Salmonella enterica subsp. enterica Serotype 4,5,12:i:− Phage Types Isolated from Swine Samples Originate from Serotype Typhimurium DT U302

Abstract: Pulsed-field gel electrophoresis, plasmid profiling, and phage typing were used to characterize and determine possible genetic relationships between 48 Salmonella enterica subsp. enterica isolates of pig origin collected in Catalonia, Spain, from 1998 to 2000. The strains were grouped into 23 multidrug-resistant fljB-lacking S. enterica serovar 4,5,12:i:؊ isolates, 24 S. enterica serovar Typhimurium isolates, and 1 S. enterica serovar 4,5,12:؊:؊ isolate. After combining the XbaI and BlnI macrorestriction profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…All of these strains contained SGI1 (4,9,10,21). By using PCR to detect class 1 integron in the SGI1, we demonstrated that all ACSSuT-type serovar Typhimurium harbored SGI1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these strains contained SGI1 (4,9,10,21). By using PCR to detect class 1 integron in the SGI1, we demonstrated that all ACSSuT-type serovar Typhimurium harbored SGI1.…”
Section: Discussionmentioning
confidence: 99%
“…The flagellar (H) antigen is expressed in the switching state between phase 1 and phase 2 antigens by the recombination event of an inverted repeat flanking the promoter region (27). Recently, monophasic H antigen expression (4,5,12:i:Ϫ) of serovar Typhimurium has been reported in phage type DT U302 (9). The mechanism that contributes to such expression change may be the inactivation of hin or one of the structural genes, fliC and fljB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…enterica serovar 4, [5],12:i:Ϫ is a worldwide emerging monophasic serovar (24). In Europe, especially, pork and its products contaminated with this serovar were identified as sources for human Salmonella infections (8,10,19). Several studies indicated that the serovar is a monophasic variant of S. enterica serovar Typhimurium lacking a genomic region that harbors the structural and regulating genes fljA, fljB, and hin encoding the second-phase flagellum (1,8,11,13,23).…”
Section: Discussionmentioning
confidence: 99%
“…This distribution is roughly representative of the serotypes isolated in our laboratory from 1997 to 2002. All isolates were epidemiologically unrelated and originated from different farms, and some had been used in previous studies (5,12).…”
Section: Methodsmentioning
confidence: 99%